Effectiveness and Tolerability of Once-Weekly GLP-1 Receptor Agonists in Clinical Practice: A Focus on Switching Between Once-Weekly Molecules in Type 2 Diabetes - Di Dalmazi, Giulia; Coluzzi, Sara; Baldassarre, Maria Pompea Antonia; Ghit, Amr; Graziano, Giusi; Rossi, Maria Chiara; Ciappini, Beatrice; Milo, Marica; Carrieri, Federica; Nicolucci, Antonio; Consoli, Agostino; Formoso, Gloria (Frontiers in Endocrinology, 2022)
Aims: To evaluate the effectiveness and tolerability of once-weekly glucagon-like peptide receptor agonists (OW GLP-1RAs) and to assess the clinical benefits of switching from one GLP-1RA to another (switchers) in a routine clinical setting. Materials and Methods: Retrospective, real-world cohort study, based on electronic medical records utilized in one Italian diabetes clinic. Estimated mean changes in HbA1c and body weight after 6 and 12 months from the first prescription of a long-acting GLP1-RA were evaluated using longitudinal linear mixed models for repeated measures. The effectiveness of the three long-acting GLP1-RAs was compared separately in the GLP1-RA naïve and switchers cohorts, after propensity score adjustment. Results: Initiating a long-acting GLP1-RA was associated with statistically significant improvements in HbA1c (-1%) and body weight (-2.6 Kg) after 6 months and benefits were maintained after 12 months. In GLP1-RA naïve cohort, semaglutide showed the largest effect on HbA1c (-1.55%; 95%CI (-1.77; -1.34) and body weight (-3.76 Kg; 95%CI -5.05; -2.47) at 6 months, maintained at 12 months (-1.55%; 95% CI-1.82;-1.28 and -6.29 Kg; 95%CI -7.94;-4.63). In the switchers' cohort, statistically significant reductions at 6 months in HbA1c and body weight were documented with semaglutide and dulaglutide only, with semaglutide associated with the most marked reduction (-0.84%; 95%CI -1.03; -0.65 and -3.43 Kg; 95% -4.67; -2.19). Drop-out rates were 9.2%, 28.5%, and 41.7% in semaglutide, dulaglutide, and exenatide groups, respectively. Conclusions: The effectiveness and tolerability of the OW GLP-1RAs in the real world were documented. Semaglutide was associated with the highest response without impact on safety. Clinical improvements were obtained even in switchers, especially in those switching to semaglutide.